2009
DOI: 10.1002/cpe.1410
|View full text |Cite
|
Sign up to set email alerts
|

Reliability in grid computing systems

Abstract: cdabrowski@nist.gov SUMMARYIn recent years, grid technology has emerged as an important tool for solving computeintensive problems within the scientific community and in industry. To further the development and adoption of this technology, researchers and practitioners from different disciplines have collaborated to produce standard specifications for implementing largescale, interoperable grid systems. The focus of this activity has been the Open Grid Forum, but other standards development organizations have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 136 publications
(33 reference statements)
0
21
0
1
Order By: Relevance
“…In particular, it will be critical to ensure that grid systems are reliable as they continue to grow in scale, exhibit greater dynamism, and become more heterogeneous in composition. In [14], the authors surveyed the work on grid reliability that has been done in recent years and reviews progress made toward achieving these goals and identified important issues and problems that researchers are working to overcome in order to develop reliability methods for large-scale, heterogeneous, dynamic environments. This work also illuminated reliability issues relating to standard specifications used in grid systems, identifying existing specifications that may need to be evolved and areas where new specifications are needed to better support the reliability.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, it will be critical to ensure that grid systems are reliable as they continue to grow in scale, exhibit greater dynamism, and become more heterogeneous in composition. In [14], the authors surveyed the work on grid reliability that has been done in recent years and reviews progress made toward achieving these goals and identified important issues and problems that researchers are working to overcome in order to develop reliability methods for large-scale, heterogeneous, dynamic environments. This work also illuminated reliability issues relating to standard specifications used in grid systems, identifying existing specifications that may need to be evolved and areas where new specifications are needed to better support the reliability.…”
Section: Related Workmentioning
confidence: 99%
“…The survey done by [4] shows that both the commercial grid systems and research grid systems that are currently in use behave reliably at present levels of scale using available technology. However, efforts to develop reliable and fault tolerant methods for grid environments are in progress with increased scale, heterogeneity, and dynamism.…”
Section: Related Workmentioning
confidence: 99%
“…Networking and computing infrastructures are subject to random resource failures. The likeliness of failures increases with the number of physical entities, as seen in large-scale distributed systems today [5], [6]. Recovering from failures becomes a critical issue to improve the reliability of the infrastructure, preventing the correct completion of many application runs.…”
Section: Addressing Production Dcis Shortcomingsmentioning
confidence: 99%